Media literacy in early education: European policies and curricular differentiation - Araújo, C. L.; Aguiar, C.; Monteiro, L. (Educational Media International, 2023)
This article is the result of work carried out within the scope of Erasmus+ project Kit@: Media competency training for professionals in day-care centres and comparable institutions in rural areas of Europe. Its main objective is to describe ECE systems, curriculum guidelines, pre-service teacher training curricula and teacher profiles related to media education and ICT use in ECE across the Europe project partners from Bulgaria, Germany, Greece, Portugal, and Slo- vakia. Data collection was carried out by documentary consultation of the curriculum guidelines of each country involved and a questionnaire on ICT use and media education in ECE, specifically developed for this purpose, answered by partners participating in the Kit@ project, and through consultation of official international reports (e.g., OECD, EURYDICE), who collected the data between January and July, 2018. Findings indicate there is a pedagogical area in all countries where the use of ICT and media education is referred to directly or indirectly in the ECE curriculum. However, in most countries, there are no guidelines for media education in initial education. Furthermore, the training of professionals and costs in ECE are quite different. Findings are discussed in terms of implications for media literacy practices in kinder-garten across Europe.